Atosiban application in fresh ET cycle is effective for women undergoing repeated embryo implantation failures, especially for advanced-age obese patients - Jie Li; Sien Mo; Zhong Lin; Qiuling Shi (Scientific Reports, 2023)
Abstract To assess the effect of atosiban in pregnancy outcomes of the fresh embryo transfer (ET), the retrospective cohort study was conducted. Six hundred and eighty-nine cases (using atosiban) and 1377 age and ET cycle-matched controls were collected from the January 2016 to May 2022 to perform the fresh IVF-ET cycle. The essential characteristics and pregnancy outcomes were analyzed. Conditional logistic regression analysis and subgroup analysis were performed. In the whole samples, atosiban had no effects in the pregnancy outcomes. Subgroup analyses suggested that atosiban could improve the clinical pregnancy in more than 3 ET cycles (OR 1.667, 95% CI 1.108–2.509, P = 0.014). Moreover, the improvement of clinical pregnancy was mainly present in the advanced-age women (age ≥ 35 years: OR 1.851, 95% CI 1.136–3.014, P = 0.013), obesity (BMI ≥ 24 kg/m2: OR 2.550, 95% CI 1.105–5.883, P = 0.028) and cleavage stage embryo (D3 embryo: OR 1.721, 95% CI 1.098–2.696, P = 0.018) among the repeated implantation failures (RIF). Atosiban could also improve the live birth for the obese women. Further, in the RIF, atosiban application was strongly recommended for the advanced-age infertility women, who also had the risk of obesity with the implantation of the cleavage stage embryo. In conclusion, atosiban could improve pregnancy outcomes for the advanced-age and obese women in RIF, especially while implanting the cleavage stage embryo in fresh ET cycle.